Etnosains Proses Pembuatan Gerabah Banyumulek sebagai Model Penguatan Karakter Berbasis Kearifan Lokal di Era Digital - Nurul Kemala Dewi; Eko Haryanto; Syakir; Muh. Fakhrihun Naam (Postgraduate, University of Mataram, 2025)
Banyumulek pottery, as one of the cultural heritages, embodies educational values that have not yet been widely revealed. This study aims to identify and analyze the character education values embedded in the process of making Banyumulek pottery. The research employs a qualitative approach with data collection techniques consisting of observation, interviews, and literature study. Data analysis is conducted through reduction, presentation, and verification. Data validation is carried out using triangulation, namely by integrating the results of interviews, observations, and document analysis. The findings show that the process of making Banyumulek pottery reflects significant character education values, such as accuracy, adherence to belief, diligence, seriousness, discipline, perseverance, mutual respect, cooperation, and creativity. This research underscores the importance of preserving the Banyumulek pottery craft and offers insights into integrating traditional values into educational practice.